Trend of traumatic crown injuries and associated factors in preschool children - Bernardo Antonio AGOSTINI; Lisara Tosatto PINTO; Mariangélica KOEHLER; Bruno EMMANUELLI; Chaiana PIOVESAN; Thiago Machado ARDENGHI
Abstract The aim of this study was to assess trends in traumatic crown injuries (TCIs), their prevalence, and association with socioeconomic and clinical factors in preschool children over a 5-year period. A series of cross-sectional surveys was conducted in Santa Maria, Brazil, on children attending a National Day of Children's Vaccination. The same protocol was used in all surveys conducted in 2008, 2010, and 2013. Clinical examinations were performed to evaluate types of traumatic crown injuries using the O'brien index. A semi-structured questionnaire was answered by the parents. It provided information about several socioeconomic factors as well as the parents' perception of their child's oral health. The chi-square for trends test was used to verify changes in TCI prevalence throughout the years. The association between socioeconomic and clinical factors with TCI was assessed by the Poisson regression analysis. A total of 1,640 children were examined. The prevalence of TCIs decreased significantly from 2008 to 2013 (10.12%; p < 0.001). Central incisors were the most vulnerable to injury, independent of the year. Moreover, older children and those with inadequate lip coverage were more likely to present with some traumatic dental injury (p < 0.001). prevalence of traumatic crown injuries decreased following the years, however TCI remain an important subject to consider when planning oral health policies.